Clinicopathologic Features and Genetic Alterations of a Primary Osteosarcoma of the Uterine Corpus. (September 2019) - Zheng, Gang; Richmond, Abby; Liu, Chengbao; Berrebi, Alexander; Pallavajjala, Aparna; Haley, Lisa; Stone, Rebecca L.; McCarthy, Edward; Vang, Russell; Xing, Deyin
Abstract : Primary osteosarcoma (OS) of the uterus is distinctly rare. We report a case of primary uterine OS with pulmonary metastasis in a 74-yr-old woman. Histopathologic features of the uterine tumor were in keeping with a pure chondroblastic OS composed of neoplastic cells with osteoblastic/chondroblastic differentiation and neoplastic bone formation. Despite treatment with Doxorubicin and Olaratumab and later with palliative radiation therapy, the patient died 7 mo after hysterectomy due to multiple distant metastases. A targeted next-generation sequencing assay based on a 637-gene panel was performed to analyze genetic alterations in this highly aggressive tumor, but no somatic mutations that are amenable to targeted therapy were detected. Rather, a 51-nucleotide deletion mutation including partial exon 2 of mediator complex subunit 12 ( MED12 ), a gene commonly mutated in leiomyoma, breast fibroadenoma and phyllodes tumor, was identified. Given the MED12 mutation in this uterine OS, we propose possible mechanisms that account for the origin and development of this tumor.